Additive manufacturing – State of art. (2020) - Rajaguru, K.; Karthikeyan, T.; Vijayan, V.
Abstract: The emerging trend of manufacturing is keenly focused on increasing the productivity. Many alternatives to enhance the productivity of a manufacturing industry involves reformation of production cycle, increasing the life of cutting tool, reducing the design complexity, etc. However, the increasing nature of size reduction and complexion in design seeks alternate method of manufacturing. The additive manufacturing is an emerging methodology used for meeting the needs of growing demand. It is a process of manufacturing parts by depositing materials which is contrary to that of conventional. The criticality involved in making full use of this technology are addressed, along with capabilities of meeting extended product requirements. It also helps in accommodating highly complex design, reduced material waste, restoring damaged parts of higher demands, etc. This work presents a complete investigational survey on various additive manufacturing techniques, integration of digital pre-processing procedures, and product-based process designing. The process of creating models with reduced development and manufacturing time is discussed in an absolute manner. Several application-based materials are described in details along with few properties at the end of rapid manufacturing.